Pasien Paska Stroke Pada Fase Subacute: Informasi Yang Dibutuhkan - Sri Hartati Pratiwi; Eka Afrima Sari; Ristina Mirwanti (Universitas Malahayati Lampung, 2022)
ABSTRACT: POST STROKE PATIENTS IN THE SUBACUTE PHASE: INFORMATION REQUIRED Introduction: Post-stroke patient care in the subacute phase is carried out independently by the patient and family at home. Post-stroke patients must have adequate knowledge to carry out self-care at home. The lack of information obtained by post-stroke patients can affect the patient's ability to carry out self-care so that his health status decreases. Therefore, nurses as educators must be able to provide information according to the needs of post-stroke patients.Purpose: This study was conducted to determine the information needs of post-stroke patients in the sub-acute phase so that the nursing care provided is in accordance with the patient's needs.Method: This study is a quantitative descriptive study conducted on post-stroke patients at the Neurology Polyclinic, one of the hospitals in Bandung. The sample technique used was consecutive sampling as many as 83 people. The inclusion criteria of post-stroke patients in this study were having full awareness and not experiencing aphasia. The instrument used in this study was based on the concept of the needs of post-stroke patients Kevitt (2009) and Moreland (2009) with a validity coefficient of 0.73 and an r of 0.75.Result: The information needs of post-stroke patients in a row include information about self-management to prevent recurrence or stroke recurrence ( = 1,59), nformation about nutrition that must be taken ( = 1,54), information about risks and side effects of treatment ( = 1,49), information about certainty of disease condition ( = 1,48), and information about stroke ( = 1,45).Conclusion: Post-stroke patients need all information related to stroke, especially regarding self-management. Therefore, health workers are expected to provide education according to patient needs. Education for stroke patients can be done using various media and focuses on the patient. Keywords: Informations needs, Subacute, Stroke Patients INTISARI: PASIEN PASKA STROKE PADA FASE SUBACUTE: INFORMASI YANG DIBUTUHKAN Latar Belakang: Perawatan pasien post stroke pada fase subacute dilakukan secara mandiri oleh pasien dan keluarga di rumah. Pasien paska stroke harus memiliki pengetahuan yang adekuat untuk menjalankan perawatan diri di rumah. Kurangnya informasi yang didapatkan pasien paska stroke dapat mempengaruhi kemampuan pasien menjalankan perawatan diri sehingga status kesehatannya menurun. Oleh karena itu, perawat sebagai edukator harus mampu memberikan informasi sesuai kebutuhan pasien paska stroke. Tujuan: Penelitian ini dilakukan untuk mengetahui kebutuhan informasi pasien paska stroke pada fase subacute agar asuhan keperawatan yang diberikan sesuai dengan kebutuhan pasien.Metoda Penelitian: Penelitian ini merupakan penelitian deskriptif kuantitatif yang dilakukan kepada pasien paska stroke di Poliklinik Saraf dua Rumah Sakit di Bandung. Teknik sample yang digunakan adalah consecutive sampling sebanyak 83 orang. Kriteria inklusi pasien paska stroke dalam penelitian ini adalah memiliki kesadaran penuh dan tidak mengalami aphasia. Instrumen yang digunakan dalam penelitian ini disusun berdasarkan konsep kebutuhan pasien paska stroke khususnya bagian kebutuhan informasi yang dikembangkan oleh Kevitt (2009) dan Moreland (2009) dengan koefisien validitas 0,73 dan r 0,75.Hasil: Kebutuhan informasi pasien paska stroke secara berturut-turut diantaranya adalah informasi mengenai manajemen diri untuk mencegah kekambuhan atau stroke ulang ( = 1,59), informasi mengenai nutrisi yang harus dijalani ( = 1,54), informasi mengenai resiko dan efek samping pengobatan ( = 1,49), informasi mengenai kepastian kondisi penyakit ( = 1,48), dan informasi mengenai penyakit stroke ( = 1,45).Kesimpulan: Pasien paska stroke membutuhkan semua informasi yang berkaitan dengan stroke khususnya mengenai manajemen diri. Oleh karena itu, petugas kesehatan diharapkan dapat memberikan edukasi sesuai dengan kebutuhan pasien. Edukasi pada pasien stroke dapat dilakukan dengan menggunakan berbagai media dan berfokus pada pasien. Kata Kunci : Kebutuhan informasi, Pasien Stroke, subacute